Peran Pemerintah Dalam Mengatur Tataniaga Garam: Dominansi Political Will atau Economic Interest? Sebuah Tinjauan Actor-Network Theory - Mumtazah Al’Amani, Yasmin; Anggono, Alexander; Tarjo (IPB University, 2024)
Conflicting interests among parties involved in the salt commodity trade create challenges. This study employs qualitative methods to investigate the interactions between human and non-human actors. The primary data used in this study was collected through in-depth interviews with relevant parties. Additionally, the triangulation method utilizes secondary data from statistical sources such as the Central Statistics Agency (BPS), related Ministries, and regulations issued by related Ministries. The results indicate that the government's efforts to regulate salt trading have primarily focused on regulations and policies related to production, distribution, and imports. However, the government has not been extensively involved in regulating market players, which include salt farmers, landowners, middlemen or trade intermediaries, consumers (including the salt processing industry and salt user industries), and salt importers. According to the perspective of actor-network theory, the government plays a significant role in organizing the interaction of actors in the salt trade. However, the existence of competing interest in the salt trade illustrates that the actors involved have systematically gathered in a network based on their economic interests.